2013
DOI: 10.1136/bmjopen-2013-003476
|View full text |Cite
|
Sign up to set email alerts
|

Cluster-randomised controlled trials of individual and combined water, sanitation, hygiene and nutritional interventions in rural Bangladesh and Kenya: the WASH Benefits study design and rationale

Abstract: IntroductionEnteric infections are common during the first years of life in low-income countries and contribute to growth faltering with long-term impairment of health and development. Water quality, sanitation, handwashing and nutritional interventions can independently reduce enteric infections and growth faltering. There is little evidence that directly compares the effects of these individual and combined interventions on diarrhoea and growth when delivered to infants and young children. The objective of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
273
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 209 publications
(279 citation statements)
references
References 135 publications
2
273
0
Order By: Relevance
“…This points to the importance of interventions that address multiple routes of transmission (i.e., WASH), an issue that has been challenged in a review that found multiple interventions, were no more effective than single interventions in community settings, 20 and is subject to an ongoing multicenter study. 21 We report elsewhere on the positive impact of the intervention on reducing absence due to diarrhea and respiratory infection 9 ; as this was a secondary outcome of the study, we did not further explore this analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This points to the importance of interventions that address multiple routes of transmission (i.e., WASH), an issue that has been challenged in a review that found multiple interventions, were no more effective than single interventions in community settings, 20 and is subject to an ongoing multicenter study. 21 We report elsewhere on the positive impact of the intervention on reducing absence due to diarrhea and respiratory infection 9 ; as this was a secondary outcome of the study, we did not further explore this analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to drinking water related covariates often controlled for in WaSH studies (e.g., household size and demographics, drinking water sources), we hypothesized that household income would be a key predictor of HWT use. 37,38 We were unable to estimate household income directly, and the governmentcollected income data we had were already aggregated at the village level. We therefore used several proxies for household income and wealth (e.g., per capita TV ownership) as well as proxies for access to services (e.g., time needed to reach the nearest health clinic).…”
Section: Methodsmentioning
confidence: 99%
“…The study's scientific objectives are to (1) determine if WASH interventions aid in early child development, (2) determine if the combination of WASH interventions is more beneficial than a single intervention alone, and (3) determine if the combination of WASH interventions plus nutrient supplements is more beneficial than any of the interventions or supplements alone. The complete main trial protocol along with its objectives and rationale have been published separately 5 ; the main study was registered at www.clinicaltrials.gov (NCT01590095 [Bangladesh] and NCT01704105 [Kenya]), and the pilot study was not separately registered. In preparation for the much larger randomized trial, the WASH Benefits project enrolled subjects in two separate but closely aligned pilot cluster, randomized trials of WASH interventions in rural western Kenya.…”
Section: Introductionmentioning
confidence: 99%